Finite element method analysis of various tooth roots on the pinion of connecting helical gear pairs having complex teeth by constant moment - Sándor, Bodzás (Journal of Production Engineering, 2022)
The aim of this study is the analysis of the mechanical parameters on the tooth roots having different fillet radiuses in case of helical gears having modified teeth. These gear pairs are widely used in different engineering constructions because of the better load transmission and the more silent noise. Consequently, the development researches are determinable in this field. Designing of one helical gear is needed for the analysis. After that the creation of its CAD model is essential. This gear pair is analyzed by different fillet radiuses on the tooth root of the pinion. All of the other geometric parameters are unchanged. The applied moments are also permanent for each experiment. After the FEM analysis the received results and graph will be evaluated.